2021
DOI: 10.3389/fpsyg.2021.743584
|View full text |Cite
|
Sign up to set email alerts
|

Shame Mediates the Relationship Between Pain Invalidation and Depression

Abstract: The experience of pain is subjective, yet many people have their pain invalidated or not believed. Pain invalidation is associated with poor mental health, including depression and lower well-being. Qualitative investigations of invalidating experiences identify themes of depression, but also social withdrawal, self-criticism, and lower self-worth, all of which are core components of shame. Despite this, no studies have quantitatively assessed the interrelationship between pain invalidation, shame, and depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
1
7
0
2
Order By: Relevance
“…Eriksen et al (2008) reported that emotion suppression, which is prevalent in Endometriosis (Zarbo et al, 2018), could result in the underreporting of depressive symptoms and mask the association between depression and pain. Stigma is another factor that could mediate the association between pain invalidation and depression (Boring et al, 2021). Further research, which controls for confounders and has longitudinal designs, is needed to elucidate the relationship between depression and pain in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eriksen et al (2008) reported that emotion suppression, which is prevalent in Endometriosis (Zarbo et al, 2018), could result in the underreporting of depressive symptoms and mask the association between depression and pain. Stigma is another factor that could mediate the association between pain invalidation and depression (Boring et al, 2021). Further research, which controls for confounders and has longitudinal designs, is needed to elucidate the relationship between depression and pain in this population.…”
Section: Discussionmentioning
confidence: 99%
“…These experiences not only have an impact on the diagnosis of this condition, which takes 8–9 years on average (Ghai et al, 2020; Tewhaiti‐Smith et al, 2022) but also increase psychological distress. For instance, feelings of pain invalidation by medical professionals have been shown to increase shame and depressive symptoms (Boring et al, 2021). Understanding the role of psychosocial factors in relation to outcomes in Endometriosis could raise awareness among healthcare professionals about their importance in the conceptualisation and management of this condition; this, in turn, can contribute to a shift from a biomedical view of the condition to a broader conceptualization that is more comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the results of other cross‐sectional studies (Garofalo et al, 2020; Leavitt et al, 2020), revealing that describing, acting with awareness, and nonjudging can act as negative predictors of aggression and NSSI by the shame‐proneness's mediating effects. Shame is considered as one variety of social pain (Boring et al, 2021; Elison et al, 2006, 2014; Iwakabe, 2021). As MacDonald and Leary (2005) hypothesizing that because social pain coopted the physical pain mechanisms, the links extend to physical threat‐defense mechanisms proposed by researchers (Jonas et al, 2014; Park et al, 2023), the results of current study can be explained by the threat‐defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…7,58 Such prevalent beliefs often go unchecked, allowing entry for bias into pain assessment and contribute to suboptimal care and continued suffering. 4,8,16,32,52 However, suspicion of others' pain has more upstream causes and is rooted in stereotypes that pervade cultural assumptions. 14 The results of our study challenge the pervasive cultural assumption that people tend to over-report pain, and indicate that normative pain reporting behavior is accurate reporting.…”
Section: Discussionmentioning
confidence: 99%